DMRT5 Together with DMRT3 Directly Controls Hippocampus Development and Neocortical Area Map Formation. (28th December 2016) - De Clercq, Sarah; Keruzore, Marc; Desmaris, Elodie; Pollart, Charlotte; Assimacopoulos, Stavroula; Preillon, Julie; Ascenzo, Sabrina; Matson, Clinton K; Lee, Melody; Nan, Xinsheng; Li, Meng; Nakagawa, Yasushi; et al.
Abstract: Mice that are constitutively null for the zinc finger doublesex and mab-3 related ( Dmrt ) gene, Dmrt5/Dmrta2, show a variety of patterning abnormalities in the cerebral cortex, including the loss of the cortical hem, a powerful cortical signaling center. In conditional Dmrt5 gain of function and loss of function mouse models, we generated bidirectional changes in the neocortical area map without affecting the hem. Analysis indicated that DMRT5, independent of the hem, directs the rostral-to-caudal pattern of the neocortical area map. Thus, DMRT5 joins a small number of transcription factors shown to control directly area size and position in the neocortex. Dmrt5 deletion after hem formation also reduced hippocampal size and shifted the position of the neocortical/paleocortical boundary. Dmrt3, like Dmrt5, is expressed in a gradient across the cortical primordium. Mice lacking Dmrt3 show cortical patterning defects akin to but milder than those in Dmrt5 mutants, perhaps in part because Dmrt5 expression increases in the absence of Dmrt3 . DMRT5 upregulates Dmrt3 expression and negatively regulates its own expression, which may stabilize the level of DMRT5. Together, our findings indicate that finely tuned levels of DMRT5, together with DMRT3, regulate patterning of the cerebral cortex.